All employees are equal, but some are more equal than others: dominance, agreeableness, and status inconsistency among men and women. Issue 3 (3rd May 2016) - Biron, Michal; De Reuver, Renee; Toker, Sharon
Abstract : Status inconsistency is a situation in which there is an objective or subjective mismatch between, for example, a person's education and his/her income. This mismatch may transform into status enhancement, wherein rewards exceed one's human capital, or into status detraction, wherein one's human capital exceeds one's rewards. Although status inconsistency affects employees' attitudes and behaviours, little is known about individual differences in this variable. The current study investigates whether the relationships of agreeableness and dominance—with objective and subjective status inconsistency vary by gender. We analysed objective and subjective input and return statuses among a sample of 375 employees. We found that men who expressed a gender-non-congruent trait, namely agreeableness, experienced an objective backlash effect compared with dominant men, whereas women who expressed a gender-non-congruent trait, namely dominance, did not experience a backlash effect compared with agreeable women. In addition, our results show that agreeable employees, both men and women, perceive themselves as status-enhanced when in fact they are not. Finally, we show that objective status inconsistency mediates the relationships of agreeableness and dominance with subjective status inconsistency.